HUBUNGAN INTENSITAS BIMBINGAN ORANG TUA DENGAN ETIKA BERBICARA REMAJA - Diwan Ramadhan Jauhari (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
The purpose of this study is to determine the relationship between the intensity of parents guidance with speaking ethic among adolescents.. This research was conducted at Madrasah TsanawiyahAlbidayah. The research design used is correlational research. The population in this study each of 162 people from students and parents with a sample of each 40 people from students and parents. Data collection techniques were conducted using a questionnaire. The correlation coefficient found was 0.421 at the medium category. So there is a moderate level of correlation between the intensity of parents guidance with speaking ethic among adolescents. The significance value (0.007) <0.05, which means there is a significant relationship between the intensity of guidance that parents do with speaking ethic among adolescents. The determinant coefficient is 0.422 = 0.1764. This can be interpreted that the influence of the intensity of guidance that parents do to speaking ethic among adolescents = 17.64%, and the remaining 82.36% determined by other factors beyond the intensity of guidance by parents. Based on the results, the authors suggest to parents to improve guidance activities to children by providing good examples. School must have guidance programs that involve parents in the process.